Dipoena torva (Thorell, 1875) – gatunek pająka związany z pniami drzew - Stańska, Marzena; Kowalczyk, Kinga; Rozwałka, Robert (Leśne Prace Badawcze, 2010)
Dipoena torva is a spider species of Euro-Siberian range, rarely recorded from many European countries and the Asian part of Russia. In Poland it is known from the 18 sites mainly located in the eastern part of the country. Literature data and new records of this spider show that this species is strictly connected with tree trunks of old trees (full of cracks and holes) and it is not as rare as it was assumed.